Mepolizumab effectiveness and identification of super-responders in severe asthma. Issue 5 (21st May 2020) - Harvey, Erin S.; Langton, David; Katelaris, Constance; Stevens, Sean; Farah, Claude S.; Gillman, Andrew; Harrington, John; Hew, Mark; Kritikos, Vicky; Radhakrishna, Naghmeh; Bardin, Philip; Peters, Matthew; et al.
Severe asthma is a high-burden disease. Real-world data on mepolizumab in patients with severe eosinophilic asthma is needed to assess whether the data from randomised controlled trials are applicable in a broader population. The Australian Mepolizumab Registry (AMR) was established with an aim to assess the use, effectiveness and safety of mepolizumab for severe eosinophilic asthma in Australia. Patients (n=309) with severe eosinophilic asthma (median age 60 years, 58% female) commenced mepolizumab. They had poor symptom control (median Asthma Control Questionnaire (ACQ)-5 score of 3.4), frequent exacerbations (median three courses of oral corticosteroids (OCS) in the previous 12 months), and 47% required daily OCS. Median baseline peripheral blood eosinophil level was 590 cells·µL −1 . Comorbidities were common: allergic rhinitis 63%, gastro-oesophageal reflux disease 52%, obesity 46%, nasal polyps 34%. Mepolizumab treatment reduced exacerbations requiring OCS compared with the previous year (annualised rate ratio 0.34 (95% CI 0.29–0.41); p<0.001) and hospitalisations (rate ratio 0.46 (95% CI 0.33–0.63); p<0.001). Treatment improved symptom control (median ACQ-5 reduced by 2.0 at 6 months), quality of life and lung function. Higher blood eosinophil levels (p=0.003) and later age of asthma onset (p=0.028) predicted a better ACQ-5 response to mepolizumab, whilst being male (p=0.031) or having body mass index ≥30 (p=0.043) predicted a lesser response. Super-responders (upper 25% of ACQ-5 responders, n=61, 24%) had a higher T2 disease burden and fewer comorbidities at baseline. Mepolizumab therapy effectively reduces the significant and long-standing disease burden faced by patients with severe eosinophilic asthma in a real-world setting. In clinical practice, mepolizumab reduces the burden of severe eosinophilic asthma by reducing severe exacerbations and improving asthma control, quality of life and lung function. Super-responders have a T2 phenotype and few comorbidities. http://bit.ly/2UIio4x